Accelerated rTMS: A Potential Treatment to Alleviate Refractory Depression - Baeken, Chris (Frontiers in Psychology, 2018)
Three decades of clinical research on repetitive Transcranial Magnetic Stimulation (rTMS) has yielded one clear treatment indication in psychiatry: major depression. Although clinical response equals standard treatment algorithms, the effect sizes on the beneficial outcome remain rather modest. Over the last couple of years, to improve efficacy in resistant depression, two new avenues have been developed: personalization and intensifying rTMS treatment. For the latter, we retrospectively compared accelerated high-frequency rTMS versus accelerated intermittent theta burst stimulation (aiTBS) in the refractory depressed state. Although clinical efficacy was not significant different between both protocols, our observations substantiate the potential of accelerated stimulation to shorten the treatment duration from the depressed state to response. Any time gain from the depressed state to recovery is in the patients’ concern.